The Role of Educational Philosophy in Human Resource Development - Taufiqurrahman, M (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to explore the role of the philosophy of education in developing more holistic human resources (HR). This research uses a qualitative approach with a library research method. The data analysis technique used is content analysis. The results showed that education is an important investment in creating a quality generation that focuses on developing skills, knowledge, and ethics. The philosophy of education, as proposed by John Dewey, emphasizes the integration of intellectual and emotional abilities to form character through experiential learning that encourages critical thinking. In addition, the philosophy of education requires a holistic approach, considering the way the material is delivered, the impact on students, and the long-term effects on society. Critical thinking, as an integral part of educational philosophy, plays an important role in developing competitive human resources in the 21st century by facilitating effective problem-solving and decision-making.